Experimental Studies on Cracking and Local Strain Behaviors of Rock-Like Materials with a Single Hole before and after Reinforcement under Biaxial Compression - Jian Liao; Yanlin Zhao; Liming Tang; Qiang Liu (Geofluids)
In deep underground engineering, circular roadways are widely used; many rock engineering problems can usually be simplified as mechanical analysis of rock structures with holes. To reveal the influence of intrahole reinforcement on the mechanical properties of rock with a single hole, this paper takes the single-hole rock-like material specimens with different reinforcement conditions as the research object. The RYL600 rock shear rheometer was used to conduct biaxial compression tests and, combined with HD industrial cameras and high-precision strain gauges, to study the effects of different reinforcement thicknesses and different lateral pressure on the mechanical properties of single-hole rock-like materials during the total stress and strain process. The thickness of the reinforced aluminum alloy pipe in the whole test is divided into four types: 0, 1, 1.5, and 2 mm. Under different reinforcement conditions, it is divided into 4 series of 0, 0.5, 1, and 1.5 MPa according to the different lateral pressure. Research shows the following: (1) Under the same lateral pressure, as the reinforcement thickness of the aluminum alloy tube increases, the reinforcement effect of the aluminum alloy tube on the specimen increases, and the strength of the reinforced specimen is increased by 1.42%~33.04% compared with the strength of the unreinforced specimen; under the same reinforced thickness of the aluminum tube, the peak strength of the specimen increases with the increase of lateral pressure, and the peak strength of the specimen with lateral pressure is 3.34%~50.26% higher than that of the specimen without lateral pressure. (2) Increasing the lateral pressure can significantly reduce the primary tensile cracks of the specimen. As the reinforcement thickness increases, the primary tensile cracks and remote cracks of the specimen are significantly reduced, and the failure surface of the specimen gradually tends to the middle of the sample. (3) The failure modes of specimens with holes can be divided into five types: single bevel type I, single bevel type II, single bevel type III, bevel T type, and single part shear type. All of these five failure modes are shear cracks that develop into fracture surfaces, while remote cracks and primary tensile cracks do not develop into fracture surfaces.